RISK MANAGEMENT OF SALAK PONDOH BUSINESS PRODUCTION IN TURI DISTRICT, SLEMAN REGENCY - Sholihah, Efi Nikmatu (Jurnal AGRISEP, 2022)
Production risk management is important for production optimization. The objectives of this study are to 1) Examine the factors that affect the production of salak pondoh farming in Sleman Regency 2) analyse the magnitude of the production risk and what are the factors that influence the production risk of salak pondoh farming in Sleman Regency, and 3) develop appropriate risk management to be applied in salak pondoh farming in Sleman Regency. The respondents of this study were 30 salak pondoh farmers in Bangunkerto Village, Turi District, Sleman Regency. Interviews with respondents were carried out in October 2021. This study were analyzed using multiple regression analysis with the Ordinary Least Square (OLS) model, while the risk level was analyzed using the coefficient of variation method. The results showed that the variables of organic fertilizer, number of workers, farming experience, plant age, and number of clumps significantly affected production. In contrast organic fertilizers and plant age have the potential to reduce the risk